Wykorzystanie rozmytej metody TOPSIS opartej na zbiorach α-poziomów do porządkowania liniowego obiektów - Łuczak, Aleksandra; Wysocki, Feliks (Application of Fuzzy TOPSIS Method Based On α-Level Sets to Linear Ordering of Objects, 2008)
The aim of this paper is to investigate the applicability of fuzzy TOPSIS method based on α- level sets to the construction of synthetic characteristics. The proposed method bases on two types of characteristic: qualitative and quantitative. The proposed procedure was employed to assess the level of people life in chosen countries in Wielkopolska province.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 337-345